Formation of a science of physical culture in Ukraine. - Timoshenko Ju.O (Kharkov National Pedagogical University, 2011)
The process of Ukrainian physical culture science institutional development is researched, its historical particularities and trends are shown. The author used only the archive data. They helped to define the structure and quality stuff of scientific institution, social and sports problems which influenced the research. It is established that the appearance of the Ukrainian Research Institute of Physical Education has identified a new trend of Soviet life.